Creativity, Art and Play Therapy - Bishop, Jay (Canadian Journal of Counselling and Psychotherapy, 2012)
Counselling is a process for learning how to create. Poetry, art and music are but three avenues open to the play therapist in optimizing self-help processes within the child. As the child composes, he monitors his activity though speaking aloud his plans and procedures. The child is both actor and monitor of the consequences of hisactions. Through listening, reading, hearing, and creating poetry, music or art, onechild learns skills for expressing his thoughts and feelings and begins to develop ways of efficiently managing them. The paper emphasizes procedures and processes that encourage portrayal of modelling by both child and adult. Use of creative events in the counselling-learning process helps children bridge the gap between fantasy and reality. Art and creativity may be the better conceptual base for counselling children and for building educational theory.